Statement by the Managing Director on the Management Implementation Plan for the IEO Report on the Fund's Performance in the Run-Up to the Crisis. (Policy Papers; Policy Paper ;, 2012)
The Management Implementation Plan puts forward a range of measures crucial to strengthening surveillance, carefully drawing on the IEO's report and on the Triennial Surveillance Review (TSR). Yet stronger surveillance cannot be cast simply in terms of technical processes, such as those for better data, risk assessments, macro-financial integration, or messaging. Deeper and more difficult questions of institutional culture, of how we conduct our daily work, are also at play, and these too need to be answered. I will focus on two aspects of the task at hand: (1) breaking down silos; and (2) promoting diverse views/candor. I would like to share with you today some initiatives that the management team has sought to implement over the past nine months, to go over the initial results, and to propose a way forward with what remains to be done.